2009
DOI: 10.4077/cjp.2009.amg070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture at Neiguan (PC 6) on Electroencephalogram

Abstract: The aim of this study was to investigate if there were any effects on the electroencephalogram (EEG) of human brain by the manual stimulation of Neiguan (PC 6) acupuncture site. In this paper, two groups of six healthy male volunteers of ages 27.6 ± 14.2 (mean ± SD) and 28.5 ± 13.0 (mean ± SD) and no neurological disease participated in this study. A digital storage of 12-channel EEG recorder was used and spectral analyses of the data set of 18 trials were obtained before, during, and after sham/ manual acupun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…2009). Neuroimaging studies have shown that acupuncture stimulation on this acupoint can modulate a wide range of cortical and limbic brain region activity (Chang et al, 2009;Quirico et al, 2014;Yoo et al, 2004;. Constant-current electrical impulses produced from a battery-driven TEAS apparatus (NDK, Osaka, Japan) were delivered on bilateral acupoints via two adhesive electrode pads placed on the acupoint skin (Fig.…”
Section: Of 29mentioning
confidence: 99%
“…2009). Neuroimaging studies have shown that acupuncture stimulation on this acupoint can modulate a wide range of cortical and limbic brain region activity (Chang et al, 2009;Quirico et al, 2014;Yoo et al, 2004;. Constant-current electrical impulses produced from a battery-driven TEAS apparatus (NDK, Osaka, Japan) were delivered on bilateral acupoints via two adhesive electrode pads placed on the acupoint skin (Fig.…”
Section: Of 29mentioning
confidence: 99%
“…To the best of our knowledge, there are no studies in scientific literature describing this phenomenon. Some reports concerning the effects on human brain EEG caused by manual needle stimulation at the PC6 acupuncture site are available [17]. These authors found that the frequency peaks in alpha band of 12 channels were more synchronized during and after acupuncture [17].…”
Section: Discussionmentioning
confidence: 99%
“…PC6 is situated between the tendons of the palmaris longus and flexor carpi radialis muscles, 2 cun proximal to the transverse crease of the wrist [16, 17]. The stimulation with red light (658 nm) was not felt by the subject.…”
Section: Methodsmentioning
confidence: 99%
“…For the correlation between PC6 acupoint stimulation and brain activation, Fu reported that both the frontal lobe and the temporal lobe were activated in varying degrees by electro-acupuncture at PC6 in the healthy group [7]. Chang founded that the amplitude and power of EEG alpha band increased during manual acupuncture when compared with the baseline data, the frequency peaks in alpha band of all 12-channels were all synchronized with much smaller standard deviation, and the manual acupuncture effects of higher power and synchronized frequencies persisted for at least 10 minutes after the experiment and did not disappear immediately for all experiments [8]. Our results were similar to the researches above.…”
Section: Discussionmentioning
confidence: 99%